How do risk preferences influence forage planting behaviors among farmers in the agro-pastoral ecotone of China? - Zhang, Wene; Khan, Aftab; Luo, Yu; Qi, Tian; Zhao, Minjuan (Frontiers in Sustainable Food Systems, 2023)
Introduction This study analyzes the influence of risk preference on the forage planting behavior of farmers in the agro-pastoral zone from three aspects-whether or not to plant forage, the scale of forage planting, and the duration of forage planting—and pays attention to the indirect effect of credit on the farmers' forage planting behavior, as well as the heterogeneity of the influence of risk preference on the forage planting behavior of farmers from the perspectives of different farming scales, types of farmers, and differences between generations. Methods Experimental economics, a two-stage model, is used to analyze this problem. Results and conclusion The results show that, first, risk preference can significantly promote farmers' forage planting probability, expand forage planting scale, and increase forage planting duration. Specifically, when risk preference increases by one unit, the probability of farmers choosing to plant forage increases by 7.8%, the planting scale increases by 0.205 hm2, and the planting duration increases by 0.519 years. This conclusion remained robust after changing the explanatory variables. Second, risk preference not only directly affects farmers' forage planting behavior but also indirectly affects farmers' forage planting behavior by influencing farmers' participation in credit. Third, heterogeneity analysis shows that risk preference has a significant effect on forage planting behavior among farmers with a medium breeding degree, among pure farmers and concurrent farmers, as well as middle-aged and elderly farmers.